Abdominoscrotal Lymphangioma Masquerading as a Communicating Hydrocele: A Case Report - AlRashed, Ahmed; Gazali, Zarine; Malladi, Vijay Kumar; Singal, Arbinder Kumar (The gulf journal of oncology, 2020)
A 5-year old boy presented with a picture of communicating hydrocele and was discovered to have an abdominoscrotal lymphangioma after undergoing hydrocele surgery. Upon initial presentation the lymphangioma was missed and the child underwent inguinal approach surgery for hydrocele. The lymphangioma was then noticed as an abdominal lump due to a rapid increase in size within 1 week following the hydrocele surgery. The sudden enlargement of the lymphangioma was due to intra-cystic hemorrhage post-operatively. The lymphangioma was then completely excised with no recurrence noted after 1 year of follow up. This is a rare case of a retroperitoneal, abdominoscrotal lymphangioma masquerading as a communicating hydrocele. Keywords: Communicating Hydrocele, Abdominoscrotal lymphangioma, Scrotal Swelling.